The Suppression of the Coagulation of Nonanticoagulated Whole Blood in vitro by Human Umbilical Endothelial Cells Cultivated on Microcarriers is not Dependent on Protein C Activation - Kohler, Hans-Peter; Müller, Michele; Bombeli, Thomas; Straub, P Werner; Haeberli, André (Thrombosis and Haemostasis, 1995)
Human umbilical vein endothelial cells (HUVEC) were cultivated on globular microcarriers in order to improve the endothelial cell surface to blood-volume ratio over the conventional flat bed cultures. HUVEC-beads were tested for their modulation of blood coagulation using a combination of two steps: HUVEC-beads were added into the syringe used for the venipuncture, in order to achieve immediate contact between cells and blood, and no anticoagulant was used during the incubation time of HUVEC-beads with whole blood. The coagulation initiation produced by venipuncture was almost completely suppressed as judged by thrombin measurements over a period of 60 min. The activated partial thromboplastin time showed a prolongation by a factor >3. Direct measurements of activated protein C (APC) were negative. Moreover, inhibition of APC-generation with a monoclonal anti-human protein C antibody did not affect the anticoagulant properties of endothelial cells. Therefore the anticoagulant properties exerted by HUVEC-beads are not dependent on APC.